A Phone-centered body sensor network platform: Cost, energy efficiency & user interface - Zhong, Lin; Sinclair, Mike; Bittner, Ray (Proceedings of the International Workshop on Body Sensor Networks, 2006)
We have designed a Bluetooth-based body sensor network platform for physiological diary applications and have addressed its challenges in cost, energy efficiency, and user interface. In our platform, an internet-capable phone serves as the center and manages every network member. We designed a Bluetooth sensor node for general sensing devices to join the network without much alteration. Since Bluetooth imposes a large power overhead, we have taken extreme care to minimize its duty cycle. We also incorporated a wrist-worn device as the user interface. It displays information under the instruction of the phone in an ambient fashion, and enables the user to interact with the network conveniently. By leveraging resources on the phone, we are able to minimize the cost and energy consumption of the sensor nodes and the wrist-worn device.